“The Young Dead Soldiers” dan “Kerawang Bekasi”: Penerjemahan sebagai Manipulasi - Prihantono, Kahar Dwi (Jurnal Penerjemahan, 2020)
This study investigates the translation of MacLeish’s poem "The Young Dead Soldiers" conducted by Chairil Anwar from two different perspectives, namely rewriting and reception perspectives. The analysis results in several findings. First, the translator manipulates most of the source poem’s features, socio-cultural context, ideology, and the poetics of the source poem so that the translator opposes the poetics of the source poem. Second, the translator alters or distorts MacLeish's intention in setting forth universal true peace by conveying the Indonesian’s armed struggle to defend the soverenity, independence, and to support to Soekarno’s government. Hence, it conforms to the ideology of the “Mimbar Indonesia” magazine, established and run by Sukarno government officials. Third, the translator also tries to present the translated poem as a new poem that is in line with the ideology of the person in chief of the "Kebudajaan" rubric in “Mimbar Indonesia” magazine who did not provide any single room for translation work. The ultimate goal of the manipulation is to provide the translation an acceptance among patrons (being published in the volume) and readers (being assumed as the original work of the translator). Fourth, both linguistic and literary equivalence cannot guarantee the success of literary translation so that the translator takes advantages of his own creativity to examine Indonesian literary infrastructure including patron, readers, ideology, poetics, economy, politics, history, and other structures upholding the Indonesian literary systems for an acceptance. Keywords: translation, poetry, manipulation, literary system.